SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN BANTUAN PINJAMAN MODAL MENGGUNAKAN METODE WEIGHTED PRODUCT MODEL (WPM) - Hartatik, Hartatik (JURNAL ILMIAH MATRIK, 2012)
SPK capital loan assistance to small and medium businesses are made by weighted product method (WPM). The criteria that are used in decision support system based on regulations in department of industry and trade. This criteria also had quantitive value. Five criteria which are used in this assesment are production, marketing, management of human resources, financial and investment feasibility. Each criteria have sub. There are four steps that are used to calculate the rank of each UMKM using weighted product model (WPM). First, calculate the value of weights for each sub criteria. Second, calculate the value of preference of each alternatives. Third, calculate the relative preference of each alternative. And the last, calculate the total score of each UMKM by multplying the value of the vector V with a percent value for each criteria. Keywords: Capital Loan, WPM, Rank Value